A Study of LGBTQ+ Empowerment and Normative Dialogue in Chinese Social Media Platforms - Xu, Yuan (Transactions on Social Science, Education and Humanities Research, 2024)
This study focuses on the empowerment and normative dialogue of LGBTQ+ groups in Chinese social media platforms, and explores its context and mechanism in the new media environment. With the popularity of social media, the LGBTQ+ community has transformed from passive receivers of information to integrated producers and participants of information, using this platform to achieve self-expression, community building, and participation in the discussion of social issues. However, there are also a number of norms in place on social media platforms that limit self-identification and expression within the LGBTQ+ community. Taking young female sexual minorities in China as an example, this study found that there are internal and external contradictions in the empowerment experiences of LGBTQ+ groups on social media. On the one hand, they achieve self-empowerment by obtaining information, expressing themselves and building communities through social media. On the other hand, they are bound by gay norms and hierarchies within the community. In response to this situation, the LGBTQ+ community has adopted a variety of resistance strategies, including rejecting identity labels, self-mockery and other ways to resist the restrictions of norms. However, these strategies also have some limitations and cannot completely escape the normative framework. Finally, this study proposes to continue gender practices in daily life and deliberately misquote norms in order to extend the boundaries of norms and provide more possibilities for self-actualization for LGBTQ+ communities.